Dietary intake at competition in elite Olympic combat sports - Pettersson, S.; Berg, C. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The purpose of the current study was to investigate elite female (n = 21) and male (n = 47) combat sports athletes' (n = 68; mean age (± SD) 21.3 ± 3.8 years; mean height 177 ± 10.2 cm) dietary intake between weigh-in and the first bout in Olympic combat sports. The data were collected at 6 separate tournaments and measurements included estimated food records, time for recovery, and body weight (BW) at weigh-in and first match. In total, 33 athletes participated in wrestling and taekwondo, sports with extended recovery times, and 35 athletes in judo and boxing, sports with limited recovery time. The results displayed that despite a mean consumption of food and drinks corresponding to 4.2 kg, the athletes only regained an average of 1.9 kg BW during recovery. Water accounted for 86% of the total intake. For each liter of water consumed, athletes gained 0.57 kg BW, when excluding heavy weight athletes (n = 5). Carbohydrate consumption was 5.5 g/kg BW, compared with the recommended 8-10 g/kg BW. In total, one-quarter of the consumed water originated from carbohydrate-rich drinks. Given the average recovery time of 18 (wrestling, taekwondo) versus 8 hr (judo, boxing), the former group consumed twice the amount of water, carbohydrates, protein, and fat as the latter group. In conclusion, a large proportion of the participants did not meet the recovery nutrition guidelines for carbohydrates. In addition, the discrepancy between nutrient intake and weight gain points to the physiological barriers to retaining fluids during a limited recovery time after engaging in weight making practices. Dietary Intake at Competition in Elite Olympic Combat Sports.